The talisman - Reed, Graham Conan (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2013)
The Talisman is an adventure story set in a future where much of today's cultural memory and technology has been lost. Following a hunting accident, a young man named Forest survives a life-threatening wound and embarks on a quest for knowledge. Rising sea levels, bands of marauders, wild animals and the perils of survival in the broken world are not the only problems facing the survivors. The nature of the collapse of the society, what triggered it and its subsequent unfolding, bequeaths an existential quandary upon them that only Forest, and a rare text as old as the earth itself, can unravel
Keywords: Fiction; Short stories; English; South Africa; Creative writing (Higher education); Short stories, South African (English) -- 21st century; South African fiction (English) -- 21st century; English language -- Writing